Analisis Location Quotient Kabupaten Kampar Tahun 2016-2020 - Shelly Meiliza (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2022)
This study aims to analyze what sectors are included in the basic and non-base sectors in encouraging economic growth in Kampar Regency in 2016-2020. This study uses secondary data obtained from the website of the Central Statistics Agency of Kampar Regency with a time span of 2016 to 2020. The analytical technique used is Location Quotient (LQ) analysis.The results of the LQ analysis show that of the 17 economic sectors, there are 4 sectors that are the basis of the sector or superior in Kampar Regency with an average LQ greater than 1, namely the agriculture, forestry and fisheries sector, mining and mining sector, real estate sector and service sector. education. These sectors are the basis of the sector or superior, meaning that these sectors have been able to meet the needs of their own regions. In general, it can also be interpreted that the base sectors are not only able to produce to meet the needs of their own regions, but are also able to provide for the needs of other regions.